Test and Treat: A New Standard for Smear-Positive Tuberculosis - Davis, J. Lucian; Dowdy, David W.; Boon, Saskia den; Walter, Nicholas D.; Katamba, Achilles; Cattamanchi, Adithya (Journal of acquired immune deficiency syndromes, 2012)
Optimizing sputum smear microscopy, the principal method of tuberculosis (TB) diagnosis in high-burden settings around the world, is a critical priority for global TB control. To improve rates of testing, completion, and reporting, the World Health Organization (WHO) recently endorsed a policy of same-day diagnosis of TB by microscopy. Unfortunately, the implementation of this policy has emphasized same-day sputum collection alone, with patients required to return on a subsequent day to collect results. We use a simple decision analysis to demonstrate that the timing of results reporting has a greater impact on treatment initiation for smear-positive TB cases than the timing of specimen collection. Same-day diagnosis of smear-positive TB, including sputum collection and reporting of smear results, should be the new global standard.
Keywords: Tuberculosis; Modeling; Decision analysis; Smear microscopy; Same-day diagnosis; Same-day treatment